Relationship between loneliness, self-esteem, and binge eating among undergraduates in Malaysia - Lim, Wei Fang; Ng, Chien Yi; Ong, Ting Wei (2023)
Numerous studies have established that loneliness and low self-esteem can contribute to the development of binge eating. This cross-sectional study aimed to investigate the predictive effects of loneliness and self-esteem on binge eating among undergraduates in Malaysia. The study recruited 147 participants aged between 18 and 25 years old, mostly female (63.9%) and of Chinese ethnicity (89.1%). The study participants were selected through purposive sampling, which involved distributing an online Qualtrics survey link and QR code through various social media platforms. The study found that both loneliness and self-esteem significantly predicted binge eating among undergraduates in Malaysia, fulfilling the study hypotheses. Multi-linear regression (MLR) analysis showed a statistically significant positive relationship between loneliness and binge eating (β = 0.215, p < .005). In addition, a statistically significant negative relationship was observed between self-esteem and binge eating (β = -0.225, p < .005). The study concludes that it fills a literature gap on the relationship between loneliness, self-esteem, and binge eating among undergraduates in Malaysia. The findings may serve as a reference for practitioners and policymakers to implement interventions and policies to alleviate binge eating problems among undergraduates in Malaysia